1998
DOI: 10.1007/s002770050379
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of toxicity and outcome in patients with acute myeloid leukemia treated with high-dose cytosine arabinoside consolidation after induction with a regimen containing idarubicin or daunorubicin

Abstract: The toxicity and outcome after high-dose ara-C/daunorubicin (HDara-C/DNR) consolidation therapy in de novo AML was compared in 11 patients who received an idarubicin-containing induction therapy (IDA; from June 1995 to March 1997) and 16 patients pretreated with daunorubicin (DNR; from July 1990 to May 1995) for induction. The DNR group consisted of two cohorts, one (n = 6) of patients who had received, as had the IDA group, two induction and one intermediate-dose ara-C consolidation courses, and another (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
5
1
Order By: Relevance
“…27 However, a German group reported that the advantage of IDR in response rate may be lost during HiDAC consolidation therapy because of increased toxicity in the IDR group. 28 However, our current study demonstrated that, among the HiDAC group, there is no difference in DFS and OS between patients receiving IDR or DNR in induction phase. In our study, although one or 2 courses of the IDR regimen were given before the HiDAC consolidation, only 19% of patients required 2 courses to obtain CR.…”
Section: Discussioncontrasting
confidence: 59%
“…27 However, a German group reported that the advantage of IDR in response rate may be lost during HiDAC consolidation therapy because of increased toxicity in the IDR group. 28 However, our current study demonstrated that, among the HiDAC group, there is no difference in DFS and OS between patients receiving IDR or DNR in induction phase. In our study, although one or 2 courses of the IDR regimen were given before the HiDAC consolidation, only 19% of patients required 2 courses to obtain CR.…”
Section: Discussioncontrasting
confidence: 59%
“…38 Patients with age Ͻ50 years received a late consolidation therapy with a high-dose AraC regimen, those with age Ͼ50 years received an intermediate-high-dose AraC regimen. Patients with promyelocytic leukemia (AML FAB M3) received a special chemotherapy protocol including all-trans retinoic acid.…”
Section: Patients and Materialsmentioning
confidence: 99%
“…All patients with de novo AML were diagnosed and treated with induction chemotherapy and consolidation therapy as described by Seipelt et al 9 Patients with secondary AML underwent induction therapy with two courses of daunorubicin or doxorubicin, ara-C and etoposide followed by consolidation therapy with one or two courses of MHD ara-C and m-AMSA or daunorubicin. Patient No.…”
Section: Chemotherapymentioning
confidence: 99%